A new species of Marmara (Lepidoptera: Gracillariidae: Marmarinae), with an Annotated List of Known Hostplants for the Genus - Eiseman, Charles S.; Davis, Donald R.; Blyth, Julia A.; Wagner, David L.; Palmer, Michael W.; Feldman, Tracy S. (Zootaxa, 2017)
Larvae of the New World gracillariid moth genus Marmara are primarily stem/bark miners, with some species mining in leaves or fruits. We describe a new species, M. viburnella Eiseman & Davis, which feeds on Viburnum, initially mining the leaves but completing development as a stem miner. The type series is from Nantucket Island, Massachusetts, with observations of leaf mines indicating the species is widespread in the eastern USA. Combining previously published data, our own observations, and other sources, we present a list of known Marmara hostplants, many of which represent undescribed species.